Qualitative study of physicians' varied uses of biomedical research in the USA. Issue 11 (21st November 2016) - Maggio, Lauren A; Moorhead, Laura L; Willinsky, John M
Abstract : Objective: To investigate the nature of physicians' use of research evidence in experimental conditions of open access to inform training and policy. Design: This qualitative study was a component of a larger mixed-methods initiative that provided 336 physicians with relatively complete access to research literature via PubMed and UpToDate, for 1 year via an online portal, with their usage recorded in web logs. Using a semistructured interview protocol, a subset of 38 physician participants were interviewed about their use of research articles in general and were probed about their reasons for accessing specific articles as identified through their web logs. Transcripts were analysed using a general inductive approach. Setting: Physician participants were recruited from and registered in the USA. Participants: 38 physicians from 16 US states, engaged in 22 medical specialties, possessing more than 1 year of experience postresidency training participated. Results: 26 participants attested to the value of consulting research literature within the context of the study by making reference to their roles as clinicians, educators, researchers, learners, administrators and advocates. The physicians reported previously encountering what they experienced as a prohibitive paywall barrier to the research literature and other frustrations with the nature of information systems, such as the need for passwords. Conclusions: The findings, against the backdrop of growing open access to biomedical research, indicate that a minority of physicians, at least initially, is likely to seek out and use research and do so in a variety of common roles. Physicians' use of research in these roles has not traditionally been part of their training or part of the considerations for open access policies. The findings have implications for educational and policy initiatives directed towards increasing the effectiveness of this access to and use of research in improving the quality of healthcare.